(3GdUdGJ GdJLGQjI Hjf HdGO GdeZQH GdGbUi h GdShOGf GdZQHj aj YUQ GdeQGHWjfs - (3GSeGA ehSi(B, (3Ydj RGjOs ((3HfZGRj(B:s (3efThQGJ LJeYI (B7 (3GcJhHQ(B,s, 2008)
(3JGQjN GdYdGbGJ GdYQHjI GdShOGfjI dOQGSI OhQ GdJLGQI aj JhKjb GhGUd GdJeGRL GdMVGQj Hjf HdGO GdeZQH GdGbUi hGdShOGf GdZQHj aj YUQ GdeQGHWjf h eOi eSGgeJgG aj GdJbOe GdMVGQjs
(3eQGLY U(B.237 (3; GdedGMb U(B.257s
Keywords: (3GdJLGQI(B- (3GdeZQH GdYQHjs; (3GdYdGbGJ GdJLGQjI(B- (3HdOGf GdeZQH GdYQHjs